RISK FACTORS FOR OSTEOPOROSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS (PRELIMINARY RESULTS ACCORDING TO THE MATERIALS OF THE MULTICENTER PROGRAM «OSTEOPOROSIS IN RHEUMATOID ARTHRITIS: DIAGNOSIS, RISK FACTORS, FRACTURES, TREATMENT») - E. A. Taskina; L. I. Alekseeva; I. S. Dydykina; M. M. Podvorotova; P. S. Dydykina; E. V. Petrova; T. A. Raskina; A. A. Muradyants; E. S. Zhugrova; D. V. Peshekhonov; A. E. Sizikov; V. N. Sorotskaya; et al. (Научно-практическая ревматология)
Osteoporosis (OP) in rheumatoid arthritis (RA) is 2–3 times more common than in the population; however, the data on the risk factors (RFs) of OP in this disease are ambiguous.Objective: to study RFs for OP in RA within the framework of the multicenter program “Osteoporosis in rheumatoid arthritis: Diagnosis, risk factors, fractures, treatment”.Subjects and methods. The trial enrolled 261 women (mean age 56.7±11.4 years) with RA; of them 151 (59%) patients were found to have OP (Group 1) and 107 (41%) were not (Group 2). All the patients underwent unified clinical, laboratory, and instrumental examination.Results. Comparison of the patients with and without OP showed that the women with OP were older (59.5±10.8 and 52.9±11.2 years, respectively; p < 0.01) had longer RA duration (14.5±9.2 and 11±8.0 years; p < 0.01), higher Health Assessment Questionnaire (HAQ) functional disability index scores (1.7±0.8 and 1.4±0.9; p < 0.01), higher C-reactive protein (CRP) levels (13.5 [7; 31] and 11 [2,7; 26] mg/l; p < 0.01); a larger number of erosions (49 [11; 90] and 8 [1;36]; p < 0.01), and a more marked joint space narrowing (112 [90; 131] and 77 [51; 102]; p < 0.01). The women with OP received longer (72 [26.5; 120] and 48 [11; 79.5] months; p < 0.01) and more frequently glucocorticoids (GC) orally (65.6 and 38.3%; p < 0.01) and as pulse therapy (41.2 and 20.4%; p < 0.01), had a larger cumulative dose (14.4 [5.4; 24.2] and 7.2 [1.5; 14.4] g; p < 0.01) and a larger GC dose at their examination (6.0 [4.0; 8,0] and 5.0 [4.0; 6.0]mg/day, respectively; p = 0.05).Conclusion. The presence of OP in RA correlates with age, RA duration, articular dysfunction, CRP levels, X-ray change magnitude, hormone therapy duration, and a cumulative GC dose.